Magnetohydrodynamic free convection and mass transfer flow past a vertical porous flat plate with Dufour and Soret effects - Maleque, Md Abdul; Alam, Md Shariful (Journal of Naval Architecture and Marine Engineering, 2009)
An analysis of free convection and mass transfer unsteady magnetohydrodynamic flow of an electrically conducting viscous incompressible fluid past an infinite vertical porous plate is presented by taking into account the Dufour and Soret effects. With a goal to attain similarity solutions of the problem posed, similarity equations are derived by introducing a time dependent length scale. The non-linear similarity equations, which are locally similar, are solved numerically using shooting method. Dimensionless velocity, temperature and concentration profiles are displayed graphically for different values of the parameters entering into the problem. Finally, the corresponding local skin-friction, local Nusselt number and local Sherwood number, which are of physical interest are tabulated. Keywords: Magnetodydrodynamic, Free convection, Mass transfer, Dufour and Soret effects. Â doi: 10.3329/jname.v1i1.2035 Journal of Naval Architecture and Marine Engineering 1(2004) 18-25